Biocontrol agent Fusarium oxysporum f.sp. strigae has no adverse effect on indigenous total fungal communities and specific AMF taxa in contrasting maize rhizospheres. (October 2016) - Zimmermann, Judith; Musyoki, Mary K.; Cadisch, Georg; Rasche, Frank
Abstract: We studied the effects of Fusarium oxysporum f.sp. strigae (Fos), a soil-borne biocontrol agent (BCA) against Striga hermonthica, on total fungal and arbuscular mycorrhizal fungal (AMF) taxa in rhizospheres of maize in both clayey and sandy soil. Effects of Fos-BCA 'Foxy-2' were evaluated against (1) S. hermonthica presence, and (2) organic fertilization with Tithonia diversifolia residues at 14, 28 and 42 d after 'Foxy-2' inoculation, via DNA-based quantitative PCR and TRFLP fingerprinting. In both soils, 'Foxy-2' occasionally promoted total fungal abundance, while the community composition was mainly altered by T. diversifolia and S. hermonthica . Notably, 'Foxy-2' stimulated AMF Gigaspora margarita abundance, while G. margarita was suppressed by S. hermonthica . Total fungal and AMF abundance were promoted by T. diversifolia residues. In conclusion, 'Foxy-2' resulted in no adverse effects on indigenous rhizosphere fungal communities substantiating its environmental safety as BCA against S. hermonthica . Highlights: 'Foxy-2' promoted AMF Gigaspora margarita abundance. Total fungal abundance was only transiently stimulated by 'Foxy-2'. Contrastingly, G. margarita abundance was suppressed by Striga hermonthica . 'Foxy-2' induced only a minor alteration of fungal community composition. 'Foxy-2' effects were generally superimposed by organic fertilization.